Case report: the role of multimodal imaging to optimize the timing of return to sports in an elite athlete with persistent COVID-19 myocardial inflammation - Daems, J. J.; van Hattum, J. C.; Pinto, Y. M.; Jørstad, H. T. (European Heart Journal - Case Reports, 2022)
Background: COVID-19 has been associated with myocardial abnormalities on cardiac magnetic resonance imaging (CMR). We report a case of COVID-19 myocarditis in an elite athlete. Case summary: A male, 21-year-old elite football player had tested positive for SARS-CoV-2 on a polymerase-chain-reaction test and was referred for cardiac evaluation after experiencing palpitations after returning to sports (RTS). Biochemical evaluation demonstrated elevated N-terminal pro b-type natriuretic peptide (NT-proBNP) and high-sensitive Troponin T. Echocardiography demonstrated left ventricular function within normal ranges for athletes but with diminished basal, posterolateral, and septal strain. Cardiac magnetic resonance imaging (CMR) showed increased T1 values and late gadolinium enhancement (LGE) in the basolateral and mid-ventricular posterior segments. Focal COVID-19 myocarditis was diagnosed and the patient remained restricted from sports, in line with the 2020 ESC sports cardiology guidelines. Two months later, his electrocardiogram (ECG) showed inferoposterolateral T-wave inversion (TWI). Serial imaging studies were performed to optimize RTS timing. Cardiac magnetic resonance imaging showed persistently increased T1/T2 values and persistent LGE at 5 and 7 months. At 9 months, 18 F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)-computerized tomography (CT) demonstrated no pathologically increased cardiac FDG-uptake. Subsequent exercise ECG and Holters demonstrated no complex ventricular arrhythmias. The patient made a complete return to elite competitive sports, without any adverse events at 15 months of follow-up. Discussion: Cardiac symptoms in athletes post-COVID-19 should prompt cardiac evaluation. As COVID-19 myocarditis inflammation can persist beyond the 3-6 months of recommended sports restriction, a more personalized approach to RTS timing can be warranted. In cases with myocardial oedema without other signs of inflammation, FDG-PET-CT can be of added value to assess active myocardial inflammation.